(3EYdGe GdYGde HCf GdeMQGH dCHj SGdes
(3ChdgG (B:s
(3CeG HYO aEf TjNfG GdYGHO GdfGUM SjOi eMeO Hf CMeO QMeg Gddg JYGdi fGhdfi hfMf HeUQ hQbI MjfFP hHg eQV GdESgGd s
(3BNQgG (B:s
(3aGYHO hJhcd Ydjg heGQHc HZGad YeG jYedhf GfJgi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B112 - (3U(B134s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(157) s
Keywords: (3GdJGQjNs